Alleviation of Hyperuricemia by Strictinin in AML12 Mouse Hepatocytes Treated with Xanthine and in Mice Treated with Potassium Oxonate - Huang, Kuo-Ching; Chang, Yu-Ting; Pranata, Rosita; Cheng, Yung-Hsuan; Chen, Yu-Chi; Kuo, Ping-Chung; Huang, Yi-Hsuan; Tzen, Jason T. C.; Chen, Rong-Jane (Biology (Basel, Switzerland), 2023)
Hyperuricemia, an abnormally high level of blood uric acid, is a major risk factor for gout. Although xanthine oxidase inhibitors were clinically used to lower blood uric acid level, the concerned side effects restricted their utilization. In this study, strictinin, an abundant polyphenol in Pu’er tea, was evaluated for its preventive effects on hyperuricemia. The results showed that the xanthine oxidase activity, uric acid production, and inflammation in AML12 mouse hepatocytes treated with xanthine were significantly reduced by the supplementation of strictinin. Detailed analyses revealed that strictinin inhibited xanthine-induced NLRP3 inflammasome activation. Consistently, the elevated blood uric acid level and the enhanced xanthine oxidase activity in mice treated with potassium oxonate were effectively diminished by strictinin supplementation. Moreover, for the first time, strictinin was found to promote healthy gut microbiota. Overall, strictinin possesses a great potential to be utilized as a functional ingredient for the prevention of hyperuricemia.